A Correlation Between Student's English Learning Activity And Reading Achievement At The Second Year Of SMA N 1 Gondang Sragen In 2011/2012 Academic Year - Ariska, Vella (2012)
The objective of this study is to find the correlation between English learning activities and the reading achievement and to know the correlation between learning activities and the reading ability. The population is all the second year students at SMA N 1 GONDANG SRAGEN in 2011/2012 Academic Year, there are 257 students of second year students in SMA N 1 Gondang Sragen, 160 females and 97 males. They are divided into 7 classes and the researchers' takes 4 classes to observe, namely XI IPS 1, XI IPS 2, XI IPS 3, and XI IPS 4 that consists of 150 students. The samples of the research are only taken from each class 30 students. This study is descriptive quantitative research. This study involves one independent variable English learning activity) that is divided into two indicators; they are reading habit and reading activity. The dependent variable is reading achievement. The data of English learning activity is collected by using a questionnaire and the reading achievement are collected by using a test. First, from the description of English learning activity, the teacher motivates the students to improve their speaking achievement. The motivation from the teachers, their parents and friends make student reading skill is good. It is based on one-way ANOVA analysis obtained that the Fcount is greater than Ftabel . So the calculating data is Fcount 2, 858 > 2, 46 Ftabel. It means that the result of statistical analysis indicates that there is correlation between English learning activity and reading achievement. For this research English learning activities develop reading achievement.